Transient surface modifications during singular heating events at diode laser facets. (29th March 2016) - Hempel, Martin; Tomm, Jens W; Bachmann, Alexander; Lauer, Christian; Furitsch, Michael; Strauß, Uwe; Elsaesser, Thomas
Abstract: Surface morphology changes and transient reflectance changes at diode laser facets are monitored during the catastrophic optical damage (COD) process in a single pulse operation. Time-resolved micro-reflectance spectroscopy with a streak-camera (time resolution ∼20 ns) allows us to observe the creation sequence of up to four distinct degradation seed points at a device facet within <300 ns. The shape of the COD seeds is created within <30–40 ns. Creation of non-planar facet areas by local melting represents the main mechanism behind the observed reflectivity changes. Subsequently the surface temperature decreases within the pulse which caused the COD.